Impact of the Covid-19 Pandemic on The European Railway Market With Special Consideration Given to Poland - Igor KAVETSKYY; Grażyna ROSA (Communications of International Proceedings, 2021)
The article presents the impact of the COVID-19 pandemic on the railway market in 2020 that is apparent in entire Europe. The decline, so noticeable in each state, regards both passenger and cargo carriage. The conducted analysis employed results of secondary research carried out by the Office of Rail Transport (https://utk.gov.pl/pl/dokumenty-i-formularze/opracowania-urzedu-tran/16878,Wplyw-pandemii-COVID-19-na-rynek-kolejowy-w-2020-r.html). The analysis leads to the conclusion that very high declines were recorded in Q2 2020 in relation to previous periods, both in passenger and cargo carriage (several dozen percent each, and in certain states - such as Ireland or United Kingdom - reaching even over 90% for passenger carriages). The outbreak of the pandemic led to a global downturn, and so a slowdown of trade, which saw a much higher decline on the rail transport market in Q2 2020. The article aims to discuss the changes on the European railway carriage market (especially the Polish one) as an aftermath of the COVID-19 coronavirus.
Keywords: COVID-19 PANDEMIC; European Railway Market; Polish Rail Market